Silica and zirconia supported tungsten, molybdenum and gallium oxide catalysts for the synthesis of furfural - Bhaumik, Prasenjit; Kane, Tanushree; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2014)
SiO2 and ZrO2 supported W, Mo and Ga oxide catalysts were prepared by a sol-gel and wet-impregnation method. The 10 wt% WO3/SiO2 (sol-gel) catalyst showed 61 +/- 2% furfural yield from hemicellulose in a one-pot fashion for at least 8 cycles. Based on XRD, TPD and Hammett acidity characterizations, the catalyst structure-activity correlation was drawn.